2020
DOI: 10.1186/s12967-020-02377-x
|View full text |Cite
|
Sign up to set email alerts
|

Development and optimization of orthotopic liver metastasis xenograft mouse models in uveal melanoma

Abstract: Background: Patients with metastatic uveal melanoma (MUM) in the liver usually die within 1 year. The development of new treatments for MUM has been limited by the lack of diverse MUM cell lines and appropriate animal models. We previously reported that orthotopic xenograft mouse models established by direct injection of MUM cells into the liver were useful for the analysis associated with tumor microenvironment in the liver. However, considering that patients with UM metastasize to the liver hematogenously, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 45 publications
(67 reference statements)
0
22
0
Order By: Relevance
“…The fact that we did not observe tumor DNA in blood may be indicative of the latter. Additional studies in uveal melanoma xenograft models that metastasize (36–38) should further assess the impact of SAMMSON knockdown on metastatic disease. Our in vitro data, based on multiple cell lines with a different genetic background, and in vivo data, based on two genetically different UM PDX models, suggest that the genetic background of the tumor does not influence the response to SAMMSON inhibition, further highlighting the broad relevance of SAMMSON inhibition as a potential therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that we did not observe tumor DNA in blood may be indicative of the latter. Additional studies in uveal melanoma xenograft models that metastasize (36–38) should further assess the impact of SAMMSON knockdown on metastatic disease. Our in vitro data, based on multiple cell lines with a different genetic background, and in vivo data, based on two genetically different UM PDX models, suggest that the genetic background of the tumor does not influence the response to SAMMSON inhibition, further highlighting the broad relevance of SAMMSON inhibition as a potential therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Cell lines from human metastatic UM are in use and their origins described elsewhere ( 84 ). Intrahepatic injection or implantation, splenic injection, intracardiac delivery or direct intravenous injection via the tail vein have been described ( 43 , 106 , 135 , 136 ). One group developed a mouse model with EGFP-luciferase-labeled human OMM1.3 cells into the retroorbital space of mice with SCID.…”
Section: Animal Models Of Metastatic Ummentioning
confidence: 99%
“…One study reported a tumor engraftment rate of 83% with this method, with the ability to follow tumors by computed tomography ( 107 ). Another study showed that splenic injections of patient-derived metastatic UM cells formed tumors diffusely throughout the liver compared to the hepatic injection that formed a single tumor ( 136 ). Additional treatments for human metastatic UM with radiotherapy, chemotherapy, gene therapy, and other agents have been explored ( 4 ).…”
Section: Animal Models Of Metastatic Ummentioning
confidence: 99%
“…The most common and reliable models for liver metastasis are splenic and portal vein injection models that consistently form hepatic metastases and are considered suitable for evaluating targeted therapies and immunotherapy based approaches (Figure 1A; panel 2) [129][130][131]. The highly consistent portal vein injection model has been used for liver metastasis in the multiple cancers including the colon, pancreas, breast, and uvea [132][133][134][135]. However, the portal vein injection model is surgically more cumbersome where a surgeon must flip all the abdominal organs to expose the portal vein.…”
Section: Mouse Models Of Metastasis and Perineural Invasionmentioning
confidence: 99%